Polyimide core-shell microspheres prepared based on Pickering emulsion method and application thereof
The thermal filler-polyimide core-shell microspheres were prepared by the Pickering emulsion method, and the thermal composite material with a three-dimensional network structure was formed by thermal molding, which solved the problem of limited improvement in thermal conductivity in the prior art and achieved efficient Thermal conductivity is improved.
Patent Information
- Application Number
- CN202411684118.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-22
AI Technical Summary
The prior art has limitations in improving the thermal conductivity of polymers, especially at low filler content, the thermal conductivity improvement of thermal composite materials is limited, resulting in limited improvement of the overall performance of the material.
The thermal filler-polyimide core-shell microspheres were prepared by using the Pickering emulsion method, and a polyimide-based thermally conductive composite material with a three-dimensional network structure was formed by thermal molding.
It achieves the maintenance of high thermal conductivity at lower filler content, improves the overall thermal conductivity of the material, and the vertical and horizontal thermal conductivity reaches 4.37W/m·K and 6.08W/m·K respectively.
Smart Images

Figure CN119463219A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer-based composite materials, and in particular relates to a thermally conductive filler-polyimide core-shell microsphere prepared based on a water-in-oil Pickering emulsion and an application thereof in a thermally conductive composite material. Background Art
[0002] In recent years, with the rapid progress of electronic integration technology, electronic equipment has gradually developed towards small size, high power and high integration, which has brought convenience to people's work and life, but it has also put forward higher requirements for the heat dissipation performance of materials. The waste heat accumulated due to insufficient heat dissipation and overheating are not conducive to the electronic equipment to maintain its original power, deteriorate its efficiency, and seriously affect the service life of electronic equipment.
[0003] To address this issue, the development of reasonable thermal conductive materials is used to solve the problem of heat accumulation. It can effectively dissipate heat and regulate the temperature of equipment, which plays a vital role in maintaining the long-term performance stability of electronic equipment, extending its service life and enhancing equipment reliability.
[0004] Polymers have the advantages of light weight, low density, low cost, high strength, corrosion resistance and easy processing, and have good application prospects in thermal conductive materials. However, most polymers have low intrinsic thermal conductivity (0.2-0.5W / m·K), making it difficult to put them into direct application. Therefore, in order to expand the application of thermal conductive polymers and thermal conductive composite materials in the field of electronics, it is very necessary to improve their thermal conductivity.
[0005] In order to prepare polyimide-based thermally conductive composite materials with good thermal conductivity, many researchers have conducted in-depth research. At present, the most common method is to use high thermal conductivity thermal conductive fillers to blend and modify common polymers. Although this method can improve the thermal conductivity of the composite material to a certain extent, simple physical blending is not conducive to the overlapping of thermal conductive fillers to form a thermal conductive path, which in turn affects the amplification efficiency of the thermal conductive filler for the material. The introduction of low-content thermal conductive fillers will cause the composite material to present a similar "island phase structure". At this time, the thermal conductive carrier with high thermal conductivity will be coated by the polymer with low thermal conductivity, which is not conducive to the improvement of the overall performance of the material. Therefore, how to maintain a high thermal conductivity of the composite material at a lower filler content is an important issue.
[0006] CN117487334A discloses a boron nitride / polyethylene thermal conductive composite film and a specific preparation method thereof. The specific operation method is: chemically crosslinking the polyethylene material, and melt blending it with boron nitride to obtain a polymer thermal conductive composite material. When the content of boron nitride nanosheets is 30wt% of the composite material, the thermal conductivity reaches 1.97W / m·K. Compared with the composite material prepared without chemical crosslinking (1.51W / m·K), it has a certain degree of improvement.
[0007] CN117987957A discloses a heat-conducting polyimide film and a preparation method thereof, wherein a fiber film is prepared by electrostatic spinning of boron nitride and polyamic acid solution, and the fiber film is immersed in PAA (polyamic acid) glue to obtain an immersed heat-conducting film. The heat-conducting film has a thermal conductivity of 1.15 W / m·K when the boron nitride content is 15 wt%.
[0008] At present, although some patents have achieved improvements in the thermal conductivity of materials, most methods are still physical blending methods, which have limited effects on improving the thermal conductivity of materials.
[0009] In summary, new technical solutions are needed to obtain high thermal conductivity composite materials. Polyimide, as a special engineering plastic, has excellent high temperature resistance. The preparation of polyimide composite materials with certain thermal conductivity has great research space and application prospects for wide application in the heat dissipation field of electronic equipment. The best solution to improve the thermal conductivity of materials is to use polyimide as the core and thermal conductive filler as the shell to prepare core-shell microspheres and then prepare composite materials. However, polyimide is often dissolved in polar solvents represented by N,N-dimethylformamide, and it is difficult to implement the preparation of core-shell microspheres through conventional solutions. In order to overcome the above shortcomings, new technical solutions need to be sought. Summary of the invention
[0010] In view of the problems existing in the prior art, the present invention provides a thermally conductive filler-polyimide core-shell microsphere prepared based on the Pickering emulsion method and its application in a thermally conductive composite material. Specifically, a water-in-oil Pickering emulsion is first prepared to prepare an emulsion droplet of a thermally conductive filler-coated polymer, and after demulsification, a thermally conductive filler-polyimide core-shell microsphere with high thermal conductivity can be obtained. Then, the core-shell microsphere is subjected to hot molding by a hot molding method to obtain a polyimide-based thermally conductive composite material with a three-dimensional network.
[0011] In a first aspect, the present invention provides a method for preparing thermal conductive filler-polyimide core-shell microspheres based on the Pickering emulsion method, wherein the method comprises the following steps:
[0012] (1) adding an aromatic diamine monomer, an aromatic dianhydride monomer and an organic polar solvent into a reaction container to react and obtain a polyamic acid solution;
[0013] (2) depositing the polyamic acid solution in water to obtain a precipitate, and then crushing, washing and drying the precipitate to obtain a polyamic acid salt precursor powder;
[0014] (3) adding the polyamic acid salt precursor powder, triethylamine and water into a reaction container to react and obtain an aqueous polyamic acid salt solution as a water phase;
[0015] (4) dispersing the thermally conductive filler and the hydrophobic polymer in a non-aqueous organic solvent to obtain an oil phase;
[0016] (5) mixing the oil phase and the water phase, and emulsifying them to obtain a water-in-oil type Pickering emulsion;
[0017] (6) transferring the water-in-oil Pickering emulsion to a precipitant for demulsification to obtain a mixture powder;
[0018] (7) Drying the mixture powder to obtain thermal conductive filler-polyimide core-shell structure microspheres.
[0019] In a second aspect, the present invention provides a thermally conductive filler-polyimide core-shell microsphere prepared by the method according to the first aspect of the present invention.
[0020] The present invention provides a method for preparing a polyimide-based thermally conductive composite material having a three-dimensional network structure in a third aspect, wherein the thermally conductive filler-polyimide core-shell microspheres described in the second aspect of the present invention are used to prepare the composite material.
[0021] In a fourth aspect, the present invention provides a polyimide-based thermally conductive composite material prepared by the method according to the third aspect of the present invention. The polyimide thermally conductive composite material has a 3D thermally conductive skeleton after hot molding, wherein the particle size of the core-shell microspheres is about 24 μm; the vertical thermal conductivity at room temperature is about 4.37 W / m·K; and the horizontal thermal conductivity is about 6.08 W / m·K.
[0022] Compared with the prior art, the present invention has the following advantages:
[0023] The present invention uses a water-in-oil Pickering emulsion method to prepare a core-shell structure of a thermally conductive filler-coated polyimide. Compared with chemical plating or chemical vapor deposition, the water-in-oil Pickering emulsion method of the present invention is more comprehensive, direct and efficient.
[0024] The present invention uses a polyamic acid salt solution as the aqueous phase and an organic dispersion containing a large-particle thermal conductive filler (the existing method generally uses a filler with a size of less than 1 micron) as the oil phase. The lipophilicity of the thermal conductive filler is improved by adding a hydrophobic polymer, and the water-oil two-phase interface of the emulsion is improved by a high-speed emulsifier, thereby preparing an oil-in-water type Pickering emulsion.
[0025] The method of the present invention does not need to add any surfactant, and achieves the balance of water and oil phases by modifying the particles, and can promote the thermal conductive filler to be coated on the surface of the aqueous droplet to form an oil-in-water structure.
[0026] The method of the present invention can form a three-dimensional thermally conductive structure of the composite material by hot molding core-shell microspheres, and exhibits excellent thermal conductivity in both the vertical and horizontal directions of the material. The emulsion method can promote the self-assembly of the connection network of the thermally conductive filler and better realize the heat transfer inside the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is the Pickering emulsion droplet morphology observed under a polarizing microscope in Example 1.
[0028] Figure 2 This is a scanning electron microscope image (SEM) of the graphene-polyimide core-shell microspheres after demulsification in Example 1.
[0029] Figure 3 This is a scanning electron microscope (SEM) image of the cross section of the graphene / polyimide composite material after hot molding in Example 1. DETAILED DESCRIPTION
[0030] Various exemplary preferred embodiments of the present invention are now described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as an illustration of certain aspects, features, and embodiments of the present invention.
[0031] In a first aspect, the present invention provides a method for preparing thermal conductive filler-polyimide core-shell microspheres based on the Pickering emulsion method, wherein the method comprises the following steps:
[0032] (1) adding an aromatic diamine monomer, an aromatic dianhydride monomer and an organic polar solvent into a reaction container to react and obtain a polyamic acid solution;
[0033] (2) depositing the polyamic acid solution in water to obtain a precipitate, and then crushing, washing and drying the precipitate to obtain a polyamic acid salt precursor powder;
[0034] (3) adding the polyamic acid salt precursor powder, triethylamine and water into a reaction container to react and obtain an aqueous polyamic acid salt solution as a water phase;
[0035] (4) dispersing the thermally conductive filler and the hydrophobic polymer in a non-aqueous organic solvent to obtain an oil phase;
[0036] (5) mixing the oil phase and the water phase, and emulsifying them to obtain a water-in-oil type Pickering emulsion;
[0037] (6) transferring the water-in-oil Pickering emulsion to a precipitant for demulsification to obtain a mixture powder;
[0038] (7) Drying the mixture powder to obtain thermal conductive filler-polyimide core-shell structure microspheres.
[0039] In step (1), an aromatic diamine monomer may be dissolved in an organic polar solvent and, while stirring, an aromatic dianhydride monomer may be added into a reaction container for reaction to obtain a polyamic acid solution.
[0040] In step (2), the polyamic acid solution can be poured into water (such as deionized water) to precipitate to obtain a white filamentous object, which is then crushed, washed, and dried to obtain a polyamic acid salt precursor powder.
[0041] In step (3), polyamic acid salt precursor powder, triethylamine and deionized water can be added into a reaction container and stirred evenly to obtain an aqueous polyamic acid salt solution (as a water phase).
[0042] In step (4), the thermally conductive filler and the hydrophobic polymer may be dispersed (for example, by stirring and / or ultrasound) in a water-insoluble organic solvent (ie, a non-aqueous organic solvent) to prepare an oil phase.
[0043] In step (5), the oil phase and the water phase may be mixed and emulsified by, for example, a high-speed emulsifier to obtain a water-in-oil (W / O) Pickering emulsion.
[0044] In some preferred embodiments, the aromatic diamine is selected from a mixture of one or more of 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 3,3'-diaminodiphenyl ether and water-soluble aromatic diamines, more preferably 4,4'-diaminodiphenyl ether. Also preferably, the water-soluble aromatic diamine is selected from a mixture of one or more of p-phenylenediamine, m-phenylenediamine and o-phenylenediamine.
[0045] The structural formulas of some specific examples of the aromatic diamines are shown below:
[0046]
[0047] In the case where the aromatic diamine is a water-soluble aromatic diamine, the above steps (1) to (3) can also be carried out in the following manner: water is added to the reactor, and then the water-soluble aromatic diamine monomer is directly dissolved in the water of the reactor, and then the aromatic dianhydride monomer and triethylamine are added to the reaction vessel to continue the reaction to obtain an aqueous polyamic acid salt solution (as the aqueous phase). Preferably, the mass ratio of the water-soluble aromatic diamine to triethylamine is 1:1 to 3:1, more preferably 2:1 to 3:1. It is also preferred that the solid content of the aqueous polyamic acid solution is controlled to be 5wt% to 20wt%, as described below.
[0048] In other preferred embodiments, the aromatic dianhydride is selected from a mixture of one or more of 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, pyromellitic anhydride and hydrogenated pyromellitic anhydride, more preferably 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride.
[0049] The structural formulas of some specific examples of the aromatic diamines are shown below:
[0050]
[0051] In other preferred embodiments, the organic polar solvent is selected from a mixture of one or more of N,N-dimethylformamide, N,N-dimethylacetamide, and dimethyl sulfoxide.
[0052] In other preferred embodiments, the thermally conductive filler is selected from a mixture of one or more of graphite, graphite nanosheets (GNPs), multi-walled carbon nanotubes (MWCNTs), graphene oxide (GO), hexagonal boron nitride (hBN), aluminum oxide (Al2O3), silicon carbide (SiC) and metal thermally conductive fillers.
[0053] Preferably, the metal thermal conductive filler is metal nanoparticles and / or a low melting point alloy. More preferably, the metal nanoparticles are selected from a mixture of one or more of silver nanoparticles, copper nanoparticles, nickel nanoparticles and iron nanoparticles, and / or the low melting point alloy is a tin-bismuth alloy and / or a liquid metal with a melting point of 20-50°C.
[0054] More preferably, the flake diameter of the graphite or boron nitride (eg, hexagonal boron nitride) is 0.5 to 10 μm.
[0055] More preferably, the graphite nanosheets have a sheet diameter of 2 μm to 10 μm and a thickness of 1 nm to 5 nm.
[0056] Furthermore, it is more preferred that the sheet diameter of the graphene oxide is 2 μm to 20 μm;
[0057] More preferably, the size of the multi-walled carbon nanotube or silicon carbide is 2 μm to 10 μm, and the diameter is 10-50 nm; the diameter of the alumina (such as spherical alumina) is 0.5-10 μm;
[0058] In other preferred embodiments, the hydrophobic polymer is selected from a mixture of one or more of decaethylene glycol, dodecanol, hexadecanol, undecanoic acid, dodecylamine, hexadecylamine, and octadecylamine, preferably hexadecylamine or octadecylamine.
[0059] In other preferred embodiments, the non-aqueous organic solvent is selected from a mixture of one or more of n-hexane, cyclohexane, toluene, xylene, dichloromethane, and chloroform, preferably xylene.
[0060] In other preferred embodiments, the precipitant is: (1) a mixture of triethylamine, acetic anhydride and ethanol; (b) a mixture of pyridine, acetic anhydride and ethanol; or (c) a mixture of pyridine, acetic anhydride and glacial acetic acid. Preferably, the mass ratio of these mixtures in the order of the above components is 1:2:(20-50).
[0061] Preferably, in step (1), the solid content of the polyamic acid solution is controlled to be 5wt%-20wt%.
[0062] More preferably, in step (2), the washing liquid used for washing is selected from a mixture of one or more of water, ethanol and isopropanol.
[0063] More preferably, in step (2), the drying temperature is 40° C.-70° C., and the drying time is 6 h to 48 h.
[0064] More preferably, in step (3), the mass ratio of the polyamic acid salt precursor powder to triethylamine is 1:1 to 3:1, and further preferably 2:1 to 3:1.
[0065] More preferably, in step (3), the mass ratio of water to the precursor powder is 100:1-5:1, more preferably 20:1 to 5:1.
[0066] More preferably, in step (3), the stirring speed is 500-1500 rpm, the stirring time is 6 h to 24 h, and the reaction temperature is room temperature.
[0067] More preferably, in step (4), the concentration of the hydrophobic polymer added to the oil phase is 10 mM to 26 mM, more preferably 16 mM to 22 mM.
[0068] More preferably, in step (4), the content of the thermally conductive filler is 5 wt % to 50 wt % of the total added amount of the thermally conductive filler and the hydrophobic polymer.
[0069] More preferably, in step (5), the volume ratio of the oil phase to the water phase is 1.5:1-20:1, more preferably 1.5:1-3:1.
[0070] More preferably, in step (5), the emulsification is carried out in an emulsifier, preferably at a speed of 10000 rpm to 20000 rpm, more preferably at a speed of 12000 rpm to 18000 rpm.
[0071] More preferably, in step (7), the drying temperature is 60°C to 100°C, preferably 60°C to 80°C, and the drying time is 2h to 30h.
[0072] The present invention uses a polyamic acid salt aqueous solution as the water phase in the emulsion to form a core structure, uses a thermally conductive filler as the oil phase in the emulsion to form a shell structure, adds a hydrophobic polymer to adjust the interface, mixes the oil phase and the water phase, and then emulsifies them through a homogenizer to obtain a Pickering emulsion, and then uses the Pickering emulsion to demulsify to obtain thermally conductive filler-polyimide core-shell microspheres.
[0073] However, in step (3), the method of the present invention is not limited to water-based polyimide salts, but is also applicable to other water-soluble polymers. The water-soluble polymers include, but are not limited to, polyvinyl alcohol, polyvinyl pyrrolidone, water-based epoxy resins, water-based polyurethanes, water-based acrylic resins, cellulose nanofibers and other polymers. The preparation of these polymers is also applicable to the method of the present invention.
[0074] In a second aspect, the present invention provides a thermally conductive filler-polyimide core-shell microsphere prepared by the method according to the first aspect of the present invention.
[0075] The present invention provides a method for preparing a polyimide-based thermally conductive composite material having a three-dimensional network structure in a third aspect, wherein the thermally conductive filler-polyimide core-shell microspheres described in the second aspect of the present invention are used to prepare the composite material.
[0076] In some preferred embodiments, the method is carried out as follows: placing the thermally conductive filler-polyimide core-shell microspheres into a vacuum hot press for hot molding to obtain the polyimide-based thermally conductive composite material having a three-dimensional network structure.
[0077] In some more preferred embodiments, the hot molding is performed in the following manner: preheating for 15 minutes, then adjusting the hydraulic jack to increase the pressure to 0.5 MPa to 20 MPa, and maintaining the temperature and pressure for 15 minutes to 25 minutes (for example, 20 minutes).
[0078] In some preferred embodiments, the hot pressing temperature of the hot molding is 300° C. to 380° C.; and / or the pressure in the vacuum chamber of the vacuum hot press is less than 10 Pa.
[0079] Alternatively, when the aqueous polyimide salt is replaced by other water-soluble polymers (such as polyvinyl alcohol, polyvinyl pyrrolidone, water-based epoxy resin, water-based polyurethane, water-based acrylic resin, cellulose nanofibers), the hot pressing temperature is 150°C-250°C.
[0080] In a fourth aspect, the present invention provides a polyimide-based thermally conductive composite material prepared by the method according to the third aspect of the present invention. The polyimide thermally conductive composite material has a 3D thermally conductive skeleton after hot molding, wherein the particle size of the core-shell microspheres can reach about 24 μm; the vertical thermal conductivity can reach about 4.37 W / m·K at room temperature; and the horizontal thermal conductivity can reach about 6.08 W / m·K.
[0081] Example
[0082] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.
[0083] Example 1: Preparation of graphene-polyimide core-shell microspheres and thermally conductive composite materials with a mass fraction of about 30 wt%
[0084] Weigh 20.023g (100mmol) of 4,4'-diaminodiphenyl ether (ODA) and 455.805g of N,N-dimethylacetamide (DMAc) and add them to a 1L three-necked flask, connect the three-necked flask to the nitrogen inlet, and continue stirring at a stirring speed of 1000r / min for 30min until the added 4,4'-diaminodiphenyl ether is completely dissolved. Then add 31.022g (100mmol) of 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride (ODPA) to the solution, stir at the same speed as above, control the reaction temperature to 20℃, and continue stirring for 12h to make ODA and ODPA react completely to obtain a polyamic acid solution with a solid content of 10wt%. The polyamic acid solution is deposited in deionized water to precipitate white filaments, which are crushed by a solid crusher at a speed of 10000r for 2min to obtain a solid powder. The solid powder was washed with 2 L of deionized water and 2 L of ethanol in sequence, and then dried in a hot air oven at 50° C. for 24 h to obtain a polyamic acid salt precursor powder.
[0085] 1 g of polyamic acid salt precursor powder and 0.476 g of triethylamine were dissolved in 10 g of deionized water to prepare a polyamic acid salt solution as the aqueous phase in the emulsion. 0.40 g of graphene (average particle size 8.2 μm) and 0.057 g (16 mM) of hexadecylamine were dispersed in 15 ml of xylene as the oil phase in the emulsion. The oil phase was added to the aqueous phase and homogenized at 13000 rpm for 2 minutes in a high-speed homogenizer to obtain an oil-in-water type Pickering emulsion (such as Figure 1 0.5 g of pyridine, 1 g of acetic anhydride and 10 g of ethanol were added to the Pickering emulsion to promote chemical imidization of the polyamic acid salt. The deposited solid filler was washed and filtered to obtain graphene-polyimide core-shell microspheres with a particle size of about 24 μm (as shown in FIG. Figure 2 shown).
[0086] The above-mentioned graphene-polyimide core-shell microspheres were placed in a hot mold, and the hot mold was placed on a vacuum hot press, the temperature was set to 320°C, the internal pressure of the vacuum chamber was controlled to be less than 10Pa, and after preheating for 15min, the hydraulic jack was adjusted to pressurize the material to 2MPa, and the heat and pressure were kept for 20min and then cooled to room temperature. 1.27g of graphene / polyimide thermal conductive composite material (such as Figure 3 shown).
[0087] When the graphene content of the composite material is 31.5wt%, the vertical thermal conductivity and the horizontal thermal conductivity are 4.37 and 6.08W / m·K respectively.
[0088] Example 2: Preparation of graphene-polyimide core-shell microspheres and thermally conductive composite materials with a mass fraction of about 10 wt%
[0089] The method is basically the same as that of Example 1, except that the content of graphene is about 10wt%. Specifically, in this example, other conditions remain unchanged, only the addition amount of graphene (average particle size 8.2μm) is changed to 0.09g, and the mass of the composite material is finally obtained to be 0.91g. When the graphene content of the composite material is 9.89wt%, the vertical thermal conductivity and horizontal thermal conductivity are 0.97 and 1.35W / m·K respectively.
[0090] Example 3: Preparation of graphene-polyimide core-shell microspheres and thermally conductive composite materials with a mass fraction of about 20 wt%
[0091] The method is basically the same as that of Example 1, except that the content of graphene is about 20wt%. Specifically, other conditions in this example remain unchanged, only the addition amount of graphene (average particle size 8.2μm) is changed to 0.2g, and the weight of the composite material finally obtained is 1.02g. When the graphene content of the composite material is 19.6wt%, the vertical thermal conductivity and horizontal thermal conductivity are 2.44 and 3.39W / m·K respectively.
[0092] Example 4: Preparation of alumina / polyimide core-shell microspheres and thermally conductive composite materials
[0093] Weigh 20.023g (100mmol) of 3,4'-diaminodiphenyl ether and 444.996g of N,N-dimethylacetamide (DMAc) into a 1L three-necked flask, connect the three-necked flask to a nitrogen inlet, and continue stirring at a stirring speed of 1000r / min for 30min until the added 3,4'-diaminodiphenyl ether is completely dissolved. Then add 29.421g (100mmol) of 3,3',4,4'-biphenyltetracarboxylic acid dianhydride (s-BPDA) to the solution, stir at the same speed as above, control the reaction temperature to 20°C, and continue stirring for 12h to complete the reaction of 3,4'-diaminodiphenyl ether and s-BPDA to obtain a polyamic acid solution with a solid content of 10wt%. The polyamic acid solution is deposited in deionized water to precipitate white filaments, which are crushed by a solid crusher at a speed of 10000r for 2min to obtain a solid powder. The solid powder was washed with 2 L of deionized water and 2 L of ethanol in sequence, and then dried in a hot air oven at 50° C. for 24 h to obtain a polyamic acid salt precursor powder.
[0094] Take 1g of polyamic acid salt precursor powder and 0.476g of triethylamine and dissolve them in 10g of deionized water to prepare a polyamic acid salt solution as the aqueous phase in the emulsion. Take 0.40g of aluminum oxide (average size 2.5μm) and 0.028g (10mM) of dodecanol and disperse them in 15ml of xylene as the oil phase in the emulsion. Add the oil phase to the aqueous phase and homogenize it in a high-speed homogenizer at 13000rpm for 2 minutes to obtain an oil-in-water type Pickering emulsion. Add 0.5g of pyridine, 1g of acetic anhydride and 10g of ethanol to the Pickering emulsion to promote chemical imidization of the polyamic acid salt, and wash the deposited solid filler with water, alcohol and filter to obtain aluminum oxide / polyimide core-shell microspheres.
[0095] Take the above-mentioned alumina / polyimide core-shell microspheres and place them in a hot mold, and place the hot mold on a vacuum hot press, set the temperature to 320°C, control the internal pressure of the vacuum chamber to be less than 10Pa, preheat for 15 minutes, adjust the hydraulic jack, pressurize the material to 2MPa, keep the heat and pressure for 20 minutes, then cool to room temperature, and take out to obtain 1.26g of alumina / polyimide thermal conductive composite material.
[0096] When the aluminum oxide content of the composite material is 31.7 wt%, the vertical thermal conductivity and the horizontal thermal conductivity are 2.44 and 2.92 W / m·K respectively.
[0097] Example 5: Preparation of Boron Nitride / Polyimide Core-Shell Microspheres and Thermally Conductive Composite Materials
[0098] Weigh 20.023g (100mmol) of 4,4'-diaminodiphenyl ether and 376.515g of N,N-dimethylacetamide (DMAc) into a 1L three-necked flask, connect the three-necked flask to the nitrogen inlet, and continue stirring at a stirring speed of 1000r / min for 30min until the added 4,4'-diaminodiphenyl ether is completely dissolved. Then add 21.812g (100mmol) of pyromellitic anhydride (PMDA) to the solution, stir at the same speed, control the reaction temperature to 20°C, continue stirring for 12h, promote the reaction to complete, and obtain a polyamic acid solution with a solid content of 10wt%. The polyamic acid solution is deposited in deionized water for a period of time, and white filaments are precipitated. After being crushed by a solid pulverizer at 10000r for 2min, a solid powder is obtained. The solid powder was washed with 2 L of deionized water and 2 L of ethanol in sequence, and then dried in a hot air oven at 50° C. for 24 h to obtain a polyamic acid salt precursor powder.
[0099] Take 1g of polyamic acid salt precursor powder and 0.476g of triethylamine and dissolve them in 10g of deionized water to prepare a polyamic acid salt solution as the water phase in the emulsion. Take 0.2g of boron nitride (average particle size 3.4μm) and 0.068g (10mM) decaethylene glycol and disperse them in 15ml of cyclohexane as the oil phase in the emulsion. Add the oil phase to the water phase and homogenize it in a high-speed homogenizer at 13000rpm for 2 minutes to obtain an oil-in-water type Pickering emulsion. Add 0.5g of pyridine and 1g of acetic anhydride to the Pickering emulsion to promote chemical imidization of the polyamic acid salt. Wash the deposited solid filler with water, alcohol, and filter it to obtain boron nitride / polyimide core-shell microspheres.
[0100] Take the above-mentioned boron nitride / polyimide core-shell microspheres and place them in a hot mold, and place the hot mold on a vacuum hot press, set the temperature to 400°C, control the internal pressure of the vacuum chamber to be less than 10Pa, preheat for 15 minutes, adjust the hydraulic jack, pressurize the material to 2MPa, keep the heat and pressure for 20 minutes, then cool to room temperature, and take out to obtain 1.04g of boron nitride / polyimide thermal conductive composite material.
[0101] When the boron nitride content of the composite material is 19.2wt%, the vertical thermal conductivity and the horizontal thermal conductivity are 1.78 and 2.67 W / m·K respectively.
[0102] Example 6: Preparation of multi-walled carbon nanotube / polyimide core-shell microspheres and thermally conductive composite materials
[0103] Weigh 20.023g (100mmol) of 4,4'-diaminodiphenyl ether and 455.805g of N,N-dimethylacetamide (DMAc) into a 1L three-necked flask, connect the three-necked flask to a nitrogen inlet, and continue stirring at a stirring speed of 1000r / min for 30min until the added 4,4'-diaminodiphenyl ether is completely dissolved. Then add 31.022g (100mmol) of 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride (ODPA) to the solution, stir at the same speed, control the reaction temperature to 20°C, continue stirring for 12h, promote the reaction to be complete, and obtain a polyamic acid solution with a solid content of 10wt%. The polyamic acid solution is deposited in deionized water for a period of time, and white filaments are precipitated. After being crushed by a solid pulverizer at 10000r for 2min, a solid powder is obtained. The solid powder was washed with 2 L of deionized water and 2 L of ethanol in sequence, and then dried in a hot air oven at 50° C. for 24 h to obtain a polyamic acid salt precursor powder.
[0104] Take 1g of polyamic acid salt precursor powder and 0.476g of triethylamine and dissolve them in 10g of deionized water to prepare a polyamic acid salt solution as the water phase in the emulsion. Take 0.2g of multi-walled carbon nanotubes (average size 7.4μm) and 0.068g (10mM) of decaethylene glycol and disperse them in 15ml of cyclohexane as the oil phase in the emulsion. Add the oil phase to the water phase and homogenize it in a high-speed homogenizer at 13000rpm for 2 minutes to obtain an oil-in-water type Pickering emulsion. Add 0.5g of pyridine and 1g of acetic anhydride to the Pickering emulsion to promote chemical imidization of the polyamic acid salt. Wash the deposited solid filler with water, alcohol and suction to obtain multi-walled carbon nanotube / polyimide core-shell microspheres.
[0105] Take multi-walled carbon nanotube / polyimide core-shell microspheres and place them in a hot mold, and place the hot mold on a vacuum hot press, set the temperature to 340°C, control the internal pressure of the vacuum chamber to be less than 10Pa, preheat for 15 minutes, adjust the hydraulic jack, pressurize the material to 2MPa, keep the heat and pressure for 20 minutes, then cool to room temperature, and take out to obtain 1.02g of boron nitride / polyimide thermal conductive composite material.
[0106] When the content of the multi-walled carbon nanotubes in the composite material is 19.6wt%, the vertical thermal conductivity and the horizontal thermal conductivity are 2.72 and 3.80W / m·K respectively.
[0107] Example 7: Preparation of silicon carbide / polyimide core-shell microspheres and thermally conductive composite materials
[0108] The method is basically the same as that of Example 1, except that the thermal conductive filler is silicon carbide (average particle size 6.7 μm); in this example, other conditions remain unchanged, only the thermal conductive filler is changed to silicon carbide, and the weight of the composite material finally obtained is 1.26 g. When the silicon carbide content of the composite material is 31.7wt%, the vertical thermal conductivity and horizontal thermal conductivity are 2.93 and 3.51 W / m·K respectively.
[0109] Example 8: Preparation of graphene-polyimide core-shell microspheres and thermally conductive composite materials
[0110] The method is basically the same as that of Example 1, except that the hydrophobic polymer is octadecylamine; in this example, other conditions remain unchanged, only the hydrophobic polymer is changed to 0.064g (16mM) octadecylamine, and the mass of the composite material finally obtained is 1.29g. When the graphene content of the composite material is 31.0wt%, the vertical thermal conductivity and the horizontal thermal conductivity are 4.26 and 5.72W / m·K respectively.
[0111] Example 9: Preparation of graphene-polyimide core-shell microspheres and thermally conductive composite materials
[0112] The method is basically the same as that of Example 1, except that the hydrophobic polymer is undecanoic acid; in this example, other conditions remain unchanged, only the hydrophobic polymer is changed: 0.047g (16mM) undecanoic acid is added, and the weight of the final composite material is 1.30g. When the graphene content of the composite material is 30.7wt%, the vertical thermal conductivity and horizontal thermal conductivity are 4.21 and 5.47W / m·K respectively.
[0113] Example 10: Preparation of graphene-polyimide core-shell microspheres and thermally conductive composite materials
[0114] The method is basically the same as that of Example 1, except that the concentration of the hydrophobic polymer is changed to 10 mM; the mass of the composite material finally obtained is 1.29 g. When the graphene content of the composite material is 31.0 wt%, the vertical thermal conductivity and the horizontal thermal conductivity are 3.25 and 4.55 W / m·K respectively.
[0115] Example 11: Preparation of graphene-polyimide core-shell microspheres and thermally conductive composite materials
[0116] The method is basically the same as that of Example 1, except that the concentration of the hydrophobic polymer is changed to 12 mM; the mass of the composite material finally obtained is 1.32 g. When the graphene content of the composite material is 30.3 wt%, the vertical thermal conductivity and the horizontal thermal conductivity are 3.58 and 5.01 W / m·K respectively.
[0117] Example 12: Preparation of graphene-polyimide core-shell microspheres and thermally conductive composite materials
[0118] The method is basically the same as that of Example 1, except that the concentration of the hydrophobic polymer is changed to 30 mM; the mass of the composite material finally obtained is 1.31 g. When the graphene content of the composite material is 30.5 wt%, the vertical thermal conductivity and the horizontal thermal conductivity are 3.53 and 5.08 W / m·K respectively.
[0119] Example 13: Preparation of graphene-polyimide core-shell microspheres and thermally conductive composite materials
[0120] The method is basically the same as that of Example 1, except that the concentration of the hydrophobic polymer is changed to 40 mM; the mass of the composite material finally obtained is 1.34 g. When the graphene content of the composite material is 29.8 wt%, the vertical thermal conductivity and the horizontal thermal conductivity are 3.13 and 4.51 W / m·K respectively.
[0121] Example 14: Preparation of graphene-polyimide core-shell microspheres and thermally conductive composite materials
[0122] The method is basically the same as that of Example 1, except that the concentration of the hydrophobic polymer is changed to 50 mM; the mass of the composite material finally obtained is 1.37 g. When the graphene content of the composite material is 29.1 wt%, the vertical thermal conductivity and the horizontal thermal conductivity are 2.77 and 3.88 W / m·K respectively.
[0123] Example 15: Preparation of graphene-polyimide core-shell microspheres and thermally conductive composite materials
[0124] The method is basically the same as that of Example 1, except that the ratio of the oil phase to the water phase is controlled to be 2:1; only the solvent in the oil phase is changed to 20 ml, and other conditions remain unchanged; the mass of the composite material finally obtained is 1.31 g. When the graphene content of the composite material is 30.5wt%, the vertical thermal conductivity and horizontal thermal conductivity are 3.87 and 5.41 W / m·K respectively. .
[0125] Example 16: Preparation of graphene-polyimide core-shell microspheres and thermally conductive composite materials
[0126] The method is basically the same as that of Example 1, except that the ratio of the oil phase to the water phase is controlled to be 4:1; only the solvent in the oil phase is changed to 40 ml, and other conditions remain unchanged; the weight of the composite material finally obtained is 1.35 g. When the graphene content of the composite material is 29.6wt%, the vertical thermal conductivity and the horizontal thermal conductivity are 3.25 and 4.62 W / m·K respectively.
[0127] Example 17: Preparation of graphene-polyimide core-shell microspheres and thermally conductive composite materials
[0128] The method is basically the same as that of Example 1, except that the ratio of the oil phase to the water phase is controlled to be 6:1; only the solvent in the oil phase is changed to 60 ml, and other conditions remain unchanged; the mass of the composite material finally obtained is 1.32 g. When the graphene content of the composite material is 30.3wt%, the vertical thermal conductivity and horizontal thermal conductivity are 2.75 and 3.91 W / m·K respectively. .
[0129] Example 18: Preparation of graphene-polyimide core-shell microspheres and thermally conductive composite materials
[0130] The method is basically the same as that of Example 1, except that the ratio of the oil phase to the water phase is controlled to be 8:1; only the solvent in the oil phase is changed to 80 ml, and other conditions remain unchanged; the mass of the composite material finally obtained is 1.34 g. When the graphene content of the composite material is 29.8wt%, the vertical thermal conductivity and horizontal thermal conductivity are 2.41 and 3.42 W / m·K respectively. .
[0131] Example 19: Preparation of graphene-polyimide core-shell microspheres and thermally conductive composite materials
[0132] The method is basically the same as that of Example 1, except that the ratio of the oil phase to the water phase is controlled to be 9:1; only the solvent in the oil phase is changed to 90 ml, and other conditions remain unchanged; the mass of the composite material finally obtained is 1.37 g. When the graphene content of the composite material is 29.1wt%, the vertical thermal conductivity and horizontal thermal conductivity are 2.04 and 2.86W / m·K respectively. .
[0133] Example 20: Preparation of graphene-polyimide core-shell microspheres and thermally conductive composite materials
[0134] The method is basically the same as that of Example 1, except that the ratio of the oil phase to the water phase is controlled to be 10:1; only the solvent in the oil phase is changed to 100 ml, and other conditions remain unchanged; the mass of the composite material finally obtained is 1.39 g. When the graphene content of the composite material is 28.7 wt%, the vertical thermal conductivity and horizontal thermal conductivity are 1.88 and 2.67 W / m·K respectively. .
[0135] Comparative Example 1: Preparation of graphene-polyimide core-shell microspheres and thermally conductive composite materials
[0136] Weigh 20.023g (100mmol) of 4,4'-diaminodiphenyl ether and 455.805g of N,N-dimethylacetamide (DMAc) into a 1L three-necked flask, connect the three-necked flask to the nitrogen inlet, and continue stirring at a stirring speed of 1000r / min for 30min until the added 4,4'-diaminodiphenyl ether is completely dissolved. Then add 31.022g (100mmol) of 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride (ODPA) to the solution, stir at the same speed as above, control the reaction temperature to 20°C, and continue stirring for 12h to allow the two to react fully to obtain a polyamic acid solution with a solid content of 10wt%. The polyamic acid solution is deposited in deionized water to precipitate white filaments, which are crushed by a solid crusher at a speed of 10000r for 2min to obtain a solid powder. The solid powder was washed with 2 L of deionized water and 2 L of ethanol in sequence, and then dried in a hot air oven at 50° C. for 24 h to obtain a polyamic acid salt precursor powder.
[0137] 1 g of polyamic acid salt precursor powder and 0.40 g of graphene were stirred in 500 ml of ethanol for 30 min to obtain a liquid mixture, and the liquid mixture was filtered, washed with water and alcohol to obtain a graphene / polyamic acid salt mixed powder.
[0138] The mixed powder described above was placed in a hot mold, and the hot mold was placed on a vacuum hot press. The temperature was set to 320°C, and the internal pressure of the vacuum chamber was controlled to be less than 10 Pa. After preheating for 15 minutes, the hydraulic jack was adjusted to pressurize the material to 2 MPa. After keeping the temperature and pressure for 20 minutes, it was cooled to room temperature and taken out to obtain 1.23 g of graphene / polyimide thermal conductive composite material.
[0139] When the graphene content of the composite material is 32.5wt%, the vertical thermal conductivity and horizontal thermal conductivity are 1.62 and 2.17W / m·K respectively.
[0140] Comparative Example 2
[0141] The method is basically the same as that of Comparative Example 1, except that the content of graphene in the composite material is about 10%. The measurement results are shown in Table 1.
[0142] Comparative Example 3
[0143] The method is basically the same as that of Comparative Example 1, except that the content of graphene in the composite material is about 20%. The measurement results are shown in Table 1.
[0144] The inventors compared the amounts of thermally conductive filler (graphene) used and the vertical thermal conductivity and horizontal thermal conductivity in Examples 1 to 3 and Comparative Examples 1 to 3, and the results are shown in Table 2.
[0145] Comparative Example 4: Preparation of graphene-polyimide core-shell microspheres and thermally conductive composite materials
[0146] Weigh 20.023g (100mmol) of 4,4'-diaminodiphenyl ether and 455.805g of N,N-dimethylacetamide (DMAc) into a 1L three-necked flask, connect the three-necked flask to the nitrogen inlet, and continue stirring at a stirring speed of 1000r / min for 30min until the added 4,4'-diaminodiphenyl ether is completely dissolved. Then add 31.022g (100mmol) of 3,3',4,4'-diphenyl ether tetraacid dianhydride (ODPA) to the solution, stir at the same speed as above, control the reaction temperature to 20℃, and continue stirring for 12h to make ODA and ODPA react completely to obtain a polyamic acid solution with a solid content of 10wt%. The polyamic acid solution is deposited in deionized water to precipitate white filaments, which are crushed by a solid crusher at a speed of 10000r for 2min to obtain a solid powder. The solid powder was washed with 2 L of deionized water and 2 L of ethanol in sequence, and then dried in a hot air oven at 50° C. for 24 h to obtain a polyamic acid salt precursor powder.
[0147] Take 1g of polyamic acid salt precursor powder and 0.476g of triethylamine and dissolve them in 10g of deionized water to prepare a polyamic acid salt solution as the aqueous phase in the emulsion. Take 0.40g of graphene (average size 800nm) and 0.057g (16mM) hexadecylamine and disperse them in 15ml of xylene as the oil phase in the emulsion. Add the oil phase to the aqueous phase and homogenize it at 13000rpm for 2 minutes in a high-speed homogenizer to obtain an oil-in-water type Pickering emulsion. Add 0.5g of pyridine, 1g of acetic anhydride and 10g of ethanol to the Pickering emulsion to promote chemical imidization of the polyamic acid salt, and wash the deposited solid filler with water, alcohol and filter it to obtain graphene-polyimide core-shell microspheres.
[0148] Take the above-mentioned graphene-polyimide core-shell microspheres and place them in a hot mold, and place the hot mold on a vacuum hot press, set the temperature to 320°C, control the internal pressure of the vacuum chamber to be less than 10Pa, preheat for 15 minutes, adjust the hydraulic jack, pressurize the material to 2MPa, keep the heat and pressure for 20 minutes, then cool to room temperature, and take out to obtain 1.29g of graphene / polyimide thermal conductive composite material.
[0149] When the graphene content of the composite material is 31.0wt%, the vertical thermal conductivity and horizontal thermal conductivity are 1.78 and 2.56W / m·K respectively.
[0150] Comparative Example 5: Preparation of graphene-polyimide core-shell microspheres and thermally conductive composite materials
[0151] The method is basically the same as that of Comparative Example 4, except that the content of graphene is about 10wt%; specifically, other conditions in this comparative example remain unchanged, only the amount of graphene added is changed to 0.09g, and the weight of the final composite material is 0.90g. When the graphene content of the composite material is 10.0wt%, the vertical thermal conductivity and the horizontal thermal conductivity are 1.37 and 1.78W / m·K respectively.
[0152] Comparative Example 6: Preparation of graphene-polyimide core-shell microspheres and thermally conductive composite materials
[0153] The method is basically the same as that of Comparative Example 4, except that the content of graphene is about 20wt%; specifically, other conditions in this comparative example remain unchanged, only the amount of graphene added is changed to 0.2g, and the weight of the final composite material is 1.02g. When the graphene content of the composite material is 19.6wt%, the vertical thermal conductivity and horizontal thermal conductivity are 0.77 and 0.92W / m·K respectively.
[0154]
[0155]
[0156]
[0157] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing thermal conductive filler-polyimide core-shell microspheres based on Pickering emulsion method, characterized in that: The method comprises the following steps: (1) adding an aromatic diamine monomer, an aromatic dianhydride monomer and an organic polar solvent into a reaction container to react and obtain a polyamic acid solution; (2) depositing the polyamic acid solution in water to obtain a precipitate, and then crushing, washing and drying the precipitate to obtain a polyamic acid salt precursor powder; (3) adding the polyamic acid salt precursor powder, triethylamine and water into a reaction container to react and obtain an aqueous polyamic acid salt solution as a water phase; (4) dispersing the thermally conductive filler and the hydrophobic polymer in a non-aqueous organic solvent to obtain an oil phase; (5) mixing the oil phase and the water phase, and emulsifying them to obtain a water-in-oil type Pickering emulsion; (6) transferring the water-in-oil Pickering emulsion to a precipitant for demulsification to obtain a mixture powder; (7) Drying the mixture powder to obtain thermal conductive filler-polyimide core-shell structure microspheres.
2. The method according to claim 1, characterized in that: The aromatic diamine is selected from a mixture of one or more of 4,4′-diaminodiphenyl ether, 3,4′-diaminodiphenyl ether, 3,3′-diaminodiphenyl ether and a water-soluble aromatic diamine, preferably 4,4′-diaminodiphenyl ether; preferably, the water-soluble aromatic diamine is selected from a mixture of one or more of p-phenylenediamine, m-phenylenediamine and o-phenylenediamine; The aromatic dianhydride is selected from a mixture of one or more of 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride, 3,3',4,4'-biphenyl tetracarboxylic dianhydride, pyromellitic anhydride and hydrogenated pyromellitic anhydride, preferably 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride; and / or The organic polar solvent is selected from a mixture of one or more of N,N-dimethylformamide, N,N-dimethylacetamide, and dimethyl sulfoxide.
3. The method according to claim 1 or 2, characterized in that: The thermally conductive filler is selected from a mixture of one or more of graphite, graphite nanosheets, multi-walled carbon nanotubes, graphene oxide, hexagonal boron nitride, aluminum oxide, silicon carbide and metal thermally conductive fillers; Preferably, the metal thermal conductive filler is metal nanoparticles and / or low melting point alloy; More preferably, the metal nanoparticles are selected from a mixture of one or more of silver nanoparticles, copper nanoparticles, nickel nanoparticles and iron nanoparticles, and / or the low melting point alloy is a tin-bismuth alloy and / or a liquid metal having a melting point of 20° C. to 50° C.; The hydrophobic polymer is selected from a mixture of one or more of decaethylene glycol, dodecanol, hexadecanol, undecanoic acid, dodecylamine, hexadecylamine, and octadecylamine, preferably hexadecylamine or octadecylamine; and / or The non-aqueous organic solvent is selected from a mixture of one or more of n-hexane, cyclohexane, toluene, xylene, dichloromethane, and chloroform, preferably xylene.
4. The method according to claim 3, characterized in that: The flake diameter of the graphite or boron nitride is 0.5 to 10 μm; The graphite nanosheet has a sheet diameter of 2 μm to 10 μm and a thickness of 1 nm to 5 nm; The sheet diameter of the graphene oxide is 2 μm to 20 μm; The size of the multi-walled carbon nanotube or silicon carbide is 2 μm to 10 μm, and the diameter is 10-50 nm; the diameter of the aluminum oxide is 0.5-10 μm.
5. The method according to any one of claims 1 to 4, characterized in that: The precipitant is: (1) a mixture of triethylamine, acetic anhydride and ethanol; (b) a mixture of pyridine, acetic anhydride and ethanol; or (c) a mixture of pyridine, acetic anhydride and glacial acetic acid; Preferably, the mass ratio of these mixed solutions according to the above component order is 1:2:(20-50).
6. The method according to any one of claims 1 to 5, characterized in that: In step (1), the solid content of the polyamic acid solution is controlled to be 5wt%-20wt%; In step (3), the mass ratio of the polyamic acid salt precursor powder to triethylamine is 1:1 to 3:1, more preferably 2:1 to 3:1; In step (3), the mass ratio of water to the precursor powder is 100:1-5:1, more preferably 20:1 to 5:1; In step (4), the hydrophobic polymer is added to the oil phase at a concentration of 10 mM to 50 mM, more preferably 16 mM to 22 mM; In step (4), the content of the thermally conductive filler is 5 wt % to 50 wt % of the total amount of the thermally conductive filler and the hydrophobic polymer added; and / or In step (5), the volume ratio of the oil phase to the water phase is 1.5:1-20:1, more preferably 1.5:1-3:
1.
7. Thermally conductive filler-polyimide core-shell microspheres prepared according to the method of any one of claims 1 to 6.
8. A method for preparing a polyimide-based thermally conductive composite material having a three-dimensional network structure, characterized in that: The method adopts the thermal conductive filler-polyimide core-shell microspheres described in claim 7 to prepare.
9. The method according to claim 8, characterized in that The method is carried out in the following manner: placing the thermally conductive filler-polyimide core-shell microspheres into a vacuum hot press for hot molding to obtain the polyimide-based thermally conductive composite material having a three-dimensional network structure; Preferably, the hot pressing temperature of the hot molding is 300° C. to 380° C.; and / or the pressure in the vacuum chamber of the vacuum hot press is less than 10 Pa; More preferably, the hot molding is performed in the following manner: preheating for 15 minutes, then adjusting the hydraulic jack to pressurize to 0.5 MPa to 20 MPa, and maintaining the temperature and pressure for 15 minutes to 25 minutes (for example, 20 minutes).
10. A polyimide-based thermally conductive composite material having a three-dimensional network structure obtained according to the method of claim 8 or 9.
Citation Information
Patent Citations
Polymer heat-conducting composite material and preparation method thereof
CN117487334A
High-thermal-conductivity and high-insulation polyimide film and preparation method thereof
CN117987957A
Polyimide microspheres and preparation method and application thereof
CN102690415A
High-thermal-conductivity polyimide film prepared from core-shell structure heat-conducting filler and preparation method of film
CN110452418A
Nano-composite porous polyimide film and preparation method thereof
CN111087634A